Pemanfaatan Teknologi Informasi Dalam Pembelajaran Pancasila Di Sekolah Dasar - Sunaryati, Titin; Siska, Falina; Rohim, Abdul; Alparidzi, Haikal; Aprindhiya, Bunga (Innovative: Journal Of Social Science Research, 2024)
The purpose of this research was to investigate and examine in more detail how primary school teachers are using technology to pique students' interest in studying Pancasila, particularly in the context of Citizenship Education (PKN). A descriptive qualitative research approach was used in this study. Articles, journals, and books are used as sources for the debate. This research aims to enhance elementary school students' engagement in Citizenship Education (PKN) by providing them with motivation and identifying areas for growth in their learning. Additionally, technology's use is crucial for fostering innovation and advancement in education. Using this IT in the classroom has the potential to revitalize the integration of tech-based outcomes into the educational process and establish it as a primary medium for teaching and learning, particularly in the context of primary school Citizenship Education (PKN) programs.